Biotechnologies for Plant Mutation Breeding 2016
DOI: 10.1007/978-3-319-45021-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Somatic Embryogenesis in Cassava

Abstract: Somatic embryogenesis, an efficient regeneration system that is being used successfully in genetic transformation, can be coupled with mutation induction to breed for cassava varieties with desired traits. The embryogenesis system requires the initiation of totipotent cells which can be used as targets for mutagenic treatments. However, initiation of these totipotent cells is low, highly genotypic dependent and has low plant conversion rate. Thus, for its successful application in mutation induction, the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In vitro regeneration through somatic embryogenesis could be useful for genetic manipulation (Elegba et al, 2021) and genome editing (Odipio et al, 2017). Somatic embryogenesis in cassava has been reported previously (Danso and Ford-Lloyd, 2002;Rossin and Rey, 2011;Ma et al, 2015;Mongomake et al, 2015;Raemakers et al, 2006;Danso and Elegba, 2017;Susanti et al, 2017;Pais, 2019). However, it is observed that somatic embryogenesis in cassava is affected by many factors such as source of explant, medium composition, culture environment, and molecules secreted by plant into medium (Nic-can et al, 2015).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In vitro regeneration through somatic embryogenesis could be useful for genetic manipulation (Elegba et al, 2021) and genome editing (Odipio et al, 2017). Somatic embryogenesis in cassava has been reported previously (Danso and Ford-Lloyd, 2002;Rossin and Rey, 2011;Ma et al, 2015;Mongomake et al, 2015;Raemakers et al, 2006;Danso and Elegba, 2017;Susanti et al, 2017;Pais, 2019). However, it is observed that somatic embryogenesis in cassava is affected by many factors such as source of explant, medium composition, culture environment, and molecules secreted by plant into medium (Nic-can et al, 2015).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 67%
“…Cassava genotypes UJ-3 and BW-1 are most preferred genotypes and widely planted by Indonesian farmers, especially in the province of Lampung (Sholihin, 2021), nonetheless the reports are scanty on somatic embryogenesis for these genotypes. Another factor which affects somatic embryogenesis in cassava is plant growth regulators (PGRs), and picloram has been reported as the best growth regulator used for inducing somatic embryo in cassava besides 2,4dichlorophenoxyacetic acid (2,4-D) (Mongomake et al, 2015;Danso and Elegba, 2017;Susanti et al, 2017).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…This approach serves as a significant experimental model for studying the processes of plant embryogenesis and is also one of the best methods for mass multiplication of elite or genetically modified plants [61]. Somatic embryos can be initiated directly or indirectly via a callus phase intervention [62]. The first somatic embryogenesis study in cassava had published in 1982 [63].…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…The first somatic embryogenesis study in cassava had published in 1982 [63]. Even though various procedures for inducing somatic embryogenesis have been established, responses to somatic embryogenesis vary considerably among genotypes [64,62], and it is also impacted by explant type and culture medium composition. Somatic embryogenesis in cassava begins with the induction of primary embryos from the explants by culturing on MS medium supplemented with auxins.…”
Section: Somatic Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation